Model-based virtual engine calibration with the help of phenomenological methods for spark-ignited engines - Grasreiner, Sebastian; Neumann, Jens; Wensing, Michael; Hasse, Christian (Applied Thermal Engineering, 2017)
High-efficiency energy conversion in modern spark-ignited combustion engines can be achieved via extensive variabilities considering the valve train, fuel injection and load control. As a significant number of parallel functionalities are required to provide control, engine calibration efforts are very high and need to be reduced by introducing virtual methods. In this paper, quasi-dimensional combustion prediction is used in combination with a gas exchange analysis to virtually calibrate the engine control unit (ECU) function for engine torque and the exhaust gas temperature. To achieve this, a phenomenological combustion model is set up. The cylinder thermodynamics, combustion-relevant turbulence and ignition delay are modeled and validated. The modeling is completed with a calculation of overall heat release rates following an entrainment approach. Targeted accuracies are met in a wide range of engine operations, especially a margin of ±6% for the high-pressure indicated work. Finally, the model's successful application is demonstrated in terms of ECU functions for the crankshaft torque and exhaust gas temperature. The virtual methodology developed can now be used in the field of ECU calibration as well as for issues where engine design is influenced by ECU calibration.
Created from Fastlane, Scopus look-up
Keywords: Model-based engine calibration; Simulation; Spark-ignited engines